You can't pay me to quit: the failure of financial incentives for smoking cessation in head and neck cancer patients. Issue 3 (15th February 2016) - Ghosh, A; Philiponis, G; Bewley, A; Ransom, E R; Mirza, N
Abstract: Objective: A prospective randomised study was conducted at a tertiary care hospital to evaluate the effects of financial incentives for smoking cessation targeted at a high-risk population. Methods: Patients with a past history of head and neck cancer were voluntarily enrolled over a two-year period. They were randomised to a cash incentives or no incentive group. Subjects were offered enrolment in smoking cessation courses. Smoking by-product levels were assessed at 30 days, 3 months and 6 months. Subjects in the incentive group received 150 if smoking cessation was confirmed. Results: Over 2 years, 114 patients with an established diagnosis of head and neck cancer were offered enrolment. Twenty-four enrolled and 14 attended the smoking cessation classes. Only two successfully quit smoking at six months. Both these patients were in the financially incentivised group and received 150 at each test visit. Conclusion: Providing a financial incentive for smoking cessation to a population already carrying a diagnosis of head and neck cancer in order to promote a positive behaviour change was unsuccessful.